2000
DOI: 10.1038/73171
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumoral action of cannabinoids: Involvement of sustained ceramide accumulation and extracellular signal-regulated kinase activation

Abstract: Delta9-Tetrahydrocannabinol, the main active component of marijuana, induces apoptosis of transformed neural cells in culture. Here, we show that intratumoral administration of Delta9-tetrahydrocannabinol and the synthetic cannabinoid agonist WIN-55,212-2 induced a considerable regression of malignant gliomas in Wistar rats and in mice deficient in recombination activating gene 2. Cannabinoid treatment did not produce any substantial neurotoxic effect in the conditions used. Experiments with two subclones of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
571
9
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(613 citation statements)
references
References 46 publications
28
571
9
5
Order By: Relevance
“…47,48 However, recent studies have shown that ERK activation may also result in cell cycle arrest, emphasizing that the responses may differ depending on the cell type and nature of the extracellular signal and its duration. [49][50][51][52] In addition, the timing and actual amounts of ZBP-89 protein generated might modulate which downstream kinase is activated. Similar to our findings with ZBP-89, overexpression of BRCA1 in MCF-7 breast cancer cells also activates both JNK (proapoptotic) and ERK (antiapoptotic) pathways, and MEK1/2 inhibition enhances BRCA1-induced apoptosis.…”
Section: Ibmentioning
confidence: 99%
“…47,48 However, recent studies have shown that ERK activation may also result in cell cycle arrest, emphasizing that the responses may differ depending on the cell type and nature of the extracellular signal and its duration. [49][50][51][52] In addition, the timing and actual amounts of ZBP-89 protein generated might modulate which downstream kinase is activated. Similar to our findings with ZBP-89, overexpression of BRCA1 in MCF-7 breast cancer cells also activates both JNK (proapoptotic) and ERK (antiapoptotic) pathways, and MEK1/2 inhibition enhances BRCA1-induced apoptosis.…”
Section: Ibmentioning
confidence: 99%
“…We have previously shown that cannabinoids inhibit the growth (Galve-Roperh et al, 2000;Sánchez et al, 2001) and angiogenesis (Blázquez et al, 2003(Blázquez et al, , 2004 of gliomas in animal models. Remarkably, this antiproliferative effect seems to be selective for brain-tumour cells as the survival of normal brain cells (astrocytes (Gómez del Pulgar et al, 2002), oligodendrocytes (Molina-Holgado et al, 2002) and neurons ) is unaffected or even favoured by cannabinoid challenge.…”
mentioning
confidence: 96%
“…Central type I CB, cloned in 1990 [26], is predominantly expressed in the brain [27], while peripheral type II CB, cloned in 1993 [28], is mainly expressed in cells of immune origin [29]. In recent years, cannabinoids, the active components of Cannabis sativa Linnaeus (Marijuana), and their derivatives have received renewed attention due to their diverse pharmacologic activities, such as cell growth inhibition, antiinflammatory effects, and tumor regression [30][31][32][33][34]. However, the molecular mechanisms by which these compounds exert their pharmacologic effects remain to be established.…”
Section: Discussionmentioning
confidence: 99%